Transportation sustainability index for Tabuk city in Saudi Arabia: an analytic hierarchy process - Al-Atawi, Attiyah M.; Kumar, Ravindra; Saleh, Wafaa (Transport, 2016)
A sustainable transport strategies for Tabuk City in the Saudi Arabia has been developed using the Analytical Hierarchy Process (AHP) using travel data collected from Tabuk City. A number of transport policies and strategies have been tested for inclusion in the developed system. The top five strategies which were ranked highest amongst these by the respondents are policies that are targeting: clean environment, altering travel behaviour, shifting to more sustainable modes of transport, charging motorists for entering the city centre and charging motorists to enter the city if the revenue raised was spent on tackling environmental pollution caused by transport. The population have been classified according to gender, age, income and family structure groups. The strategy of promoting clean environment policies were high priority while for example, charging motorists to enter the city if the revenue raised was spent on tackling environmental pollution policies were not popular for any group. Priority ranking of transport sustainability at pre- and post-implementation stages of the transportation measure are important to provide recommendations for implementation. The strength of this approach is mainly in its ability to perform decision making under limited, heterogeneous data coming from multiple stakeholders which is presented in terms of different types of user group in our case study. This research can be further enhanced by testing further population groups and increasing the sample size.First published online: 13 Jul 2015